Smart grids and electric vehicles: Made for each other? - Trevor Morgan (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2012)
Electric vehicles (EVs) could play a central role in decarbonising road transport. But this new type of electricity load will need careful management. Although electricity needs for EVs are likely to remain small relative to overall load in most regions for many years to come, they could have a much bigger impact on peak load as motorists seek to recharge their batteries during the evening. Electricity suppliers will need to anticipate the long-term investments that will be needed to respond to this emerging trend. (...)
Keywords: 330